2000
DOI: 10.1128/aem.66.6.2536-2540.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Volatile Fatty Acids in Development of the Cecal Microflora in Broiler Chickens during Growth

Abstract: It is known that volatile fatty acids can inhibit growth of species of the family Enterobacteriaceae in vitro. However, whether these volatile fatty acids affect bacterial populations in the ceca of chickens is unknown. Therefore, a study was conducted to investigate if changes in volatile fatty acids in ceca of broiler chickens during growth affect bacterial populations. Results showed that members of the Enterobacteriaceae and enterococci are present in large numbers in 3-day-old broilers and start to decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
197
2
14

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(232 citation statements)
references
References 24 publications
11
197
2
14
Order By: Relevance
“…Elsewhere, enterococci were shown to exist in caecal contents of chicks at a concentration of 1.32Â10 8 CFU g À1 (Spring et al, 2000). Another group, analyzing the development of caecal microbiota in chickens during growth, noted that on day 35, chicks contained an average of 10 7 CFU g À1 enterococci (van der Wielen et al, 2000). These findings correlate with our results from culturing studies.…”
Section: Linearity Of Dilution -Enterococcus Faecalissupporting
confidence: 82%
“…Elsewhere, enterococci were shown to exist in caecal contents of chicks at a concentration of 1.32Â10 8 CFU g À1 (Spring et al, 2000). Another group, analyzing the development of caecal microbiota in chickens during growth, noted that on day 35, chicks contained an average of 10 7 CFU g À1 enterococci (van der Wielen et al, 2000). These findings correlate with our results from culturing studies.…”
Section: Linearity Of Dilution -Enterococcus Faecalissupporting
confidence: 82%
“…Major factors affecting microbial number and composition along the length of the intestine appear to be age, diet, and host genotype (van der Wielen et al, 2000;Apajalahti et al, 2001;Hill et al, 2005). Comparisons between the zoo animals described previously revealed that diet was the strongest determining factor in shaping microbial composition, where animals were grouped based on whether they were carnivores, herbivores, or omnivores.…”
Section: Factors Affecting the Gut Microbiomementioning
confidence: 99%
“…For infections which may occur before this time, such as those arising Colonisation-inhibition, or competitive exclusion, as it is more commonly known, can also be induced by the administration of normal gut flora preparations to newly hatched chicks. Young birds are highly susceptible to infection with Salmonella, as a consequence of the absence of a protective gut flora and immaturity of the immune system (Friedman et al, 2003;van der Wielen et al, 2000). The first can be overcome by the application of competitive exclusion (CE) products based on cultures of normal flora obtained from pathogen-free adult birds (Nurmi & Rantala, 1973), which, according to the recommendation of the WHO, should be applied as early as possible to day-old chicks in the hatchery or by spraying eggs and in preference to administration via the first drinking water.…”
Section: Colonisation-inhibitionmentioning
confidence: 99%